2022
DOI: 10.3390/foods11182900
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone Colorimetric Sensor Based on Pt@Au Nanozyme for Visual and Quantitative Detection of Omethoate

Abstract: A smartphone colorimetric sensor based on the Pt@Au nanozyme was successfully developed for the visual and quantitative detection of omethoate in fruit and vegetables. The anti-omethoate antibody was conjugated on the surface of the Pt@Au nanozyme as a catalytic functional signal probe, and coating antigen conjugated on the surface of magnetic polystyrene microspheres (MPMs) was used as a separation capture probe. In the sensing system, when the catalytic functional signal probe was combined with a separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The pomegranate seed-structured bimetallic gold–platinum nanomaterials (Ps-PtAu NPs) were prepared at room temperature according to the previous literature. 31 As shown in Fig. 1A, TEM demonstrated that the synthesized Ps-PtAu NPs had a well-defined spherical pomegranate seed shape with a uniform diameter of around 15.12 ± 1.6 nm (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The pomegranate seed-structured bimetallic gold–platinum nanomaterials (Ps-PtAu NPs) were prepared at room temperature according to the previous literature. 31 As shown in Fig. 1A, TEM demonstrated that the synthesized Ps-PtAu NPs had a well-defined spherical pomegranate seed shape with a uniform diameter of around 15.12 ± 1.6 nm (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…These findings suggested good oxidative mimicking activity of Ps-PtAu NPs. 31 As the concentration of Ps-PtAu NPs co-incubated with TMB increased, obvious and significant enhancement in the UV-vis absorbance spectrum was observed (Fig. 2B).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Integrated with the smartphone Apps featuring powerful computing and analysis capabilities, the signal intensities could be transferred to the data directly reflecting the analyte concentration. [55][56][57] For example, S. Lee and coworkers reported Fe-doped carbon dots (FeCDs) with peroxidase (POD)-mimic activity, which were further used to establish a portable smartphone-nanopaper integrated sensing platform to monitor hydrogen peroxide (H 2 O 2 ). [49] H 2 O 2 was decomposed into reactive hydroxyl radicals ( * OH) by the FeCDs nanozyme catalysis, which continuously oxidized the colorless TMB to generate a blue oxidization product (oxTMB).…”
Section: Colorimetric Signalmentioning
confidence: 99%
“…In addition, the illegal additives such as industrial alcohol, βestradiol, melamine, etc., are also involved in nanozyme-based food analysis. [57,140]…”
Section: Food Contaminant Analysismentioning
confidence: 99%